2019
DOI: 10.1002/jctb.6145
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal phytoremediation of a poplar clone in a contaminated soil in southern Italy

Abstract: BACKGROUND The Monviso clone previously tested successfully to remediate a lindane‐contaminated soil in central Italy was then applied in a historically heavy metal contaminated area in southern Italy. RESULTS The results obtained at 900 days from the poplar planting showed a strong decrease below Italian national legal limits (D.Lgs 152/06) for most heavy metals (HMs). The highest reduction of HM concentrations was observed in soil samples collected near the trunk (25 cm distant from poplar) and in the rhizos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 76 publications
(171 reference statements)
2
24
0
1
Order By: Relevance
“…sugars, polysaccharides, amino acids, aromatic acids, aliphatic acids, fatty acids, sterols, phenolic compounds, enzymes, proteins, plant growth regulators and secondary metabolites) which attract soil microorganisms into the rhizosphere where they multiply by several orders of magnitude [28]. In turn, microorganisms strongly in uence plant development and health by mineralizing organic matter, degrading organic pollutants, including persistent ones such as PCBs, improving heavy metal bioavailability by varying the degree of reaction of the soil (pH), releasing chelating substances (organic acids, siderophores) and promoting oxidation/reduction reactions [8,20]. In line with the above, the DNA sequencing data showed higher percentages of bacteria genera (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sugars, polysaccharides, amino acids, aromatic acids, aliphatic acids, fatty acids, sterols, phenolic compounds, enzymes, proteins, plant growth regulators and secondary metabolites) which attract soil microorganisms into the rhizosphere where they multiply by several orders of magnitude [28]. In turn, microorganisms strongly in uence plant development and health by mineralizing organic matter, degrading organic pollutants, including persistent ones such as PCBs, improving heavy metal bioavailability by varying the degree of reaction of the soil (pH), releasing chelating substances (organic acids, siderophores) and promoting oxidation/reduction reactions [8,20]. In line with the above, the DNA sequencing data showed higher percentages of bacteria genera (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals (HMs) are "trace elements" in pristine ecosystems, whereas their concentrations increase when there are anthropogenic activities (steel industry, waste disposal, agriculture, mining). HMs pose a risk owing to their toxicity, bioaccumulation and biomagni cation [4]; they cause cell oxidative stress through formation of free radicals and are able to replace essential metals in pigments or enzymes, with consequent disruption of their functions [5,6]. PCBs and HMs are frequently found as soil cocontaminants [7,8], posing a risk for both ecosystems and human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of heavy metals from soil and the improvement of its quality was also the main objective of another paper by Ancona et al, who presented a poplar-based phytoremediation method. 6 This work highlighted a specific plant species that favours the phytostabilization of heavy metals, as a consequence of complex interactions generated between the plant and the rhizosphere microorganisms. The result is an overall improvement of soil quality in relation to organic carbon content and microbial activity.…”
mentioning
confidence: 99%
“…Upon investigating various operational conditions, authors concluded that those bacteria may actually protect plants with a simultaneous decrease in metals accumulation. The elimination of heavy metals from soil and the improvement of its quality was also the main objective of another paper by Ancona et al ., who presented a poplar‐based phytoremediation method . This work highlighted a specific plant species that favours the phytostabilization of heavy metals, as a consequence of complex interactions generated between the plant and the rhizosphere microorganisms.…”
mentioning
confidence: 99%